EFFECTS OF BASIC LIFE SUPPORT TRAINING AMONG NON-MEDICAL UNIVERSITY STAFF IN GHANA - Prah, James; Afrifa , Alex; Antwi , Eugene; Ninfah, Seth; Ghansah , Augustus; Annor , Akua (African Journal of Research in Medical and Health Sciences, 2025)
Background: Timely bystander intervention during cardiac emergencies significantly improves survival, yet Basic Life Support (BLS) knowledge and readiness remain low among non-medical populations. Universities are dynamic environments where non-clinical staff may become first responders in emergencies. This study assessed BLS knowledge, attitudes, and practices (KAP) among non-medical staff at the University of Cape Coast (UCC), evaluated the impact of a structured BLS training, and identified predictors of knowledge improvement. Methods: A quasi-experimental pre-post design was employed among 309 randomly selected non-health staff. Participants completed a validated KAP questionnaire and a 10-item BLS knowledge test before and after a four-hour instructor-led training session. Data were analyzed using t-tests, ANOVA, Pearson correlation, and multiple linear regression. Results: The mean pre-test score was 5.18 (SD = 2.03), rising significantly to 9.34 (SD = 1.17) post-training (p < .001). Knowledge gains were consistent across age and sex. Pre-test performance negatively correlated with age (r = -0.113, p = .047), but this association was not observed post-training. Regression analysis revealed that pre-test score (β = -0.73, p < .001) and belonging to the “Others” staff category (β = -1.64, p < .001) significantly predicted lower gain scores. All participants endorsed the importance of BLS training, though barriers like lack of knowledge and fear of causing harm persisted. Conclusion: BLS training significantly improved knowledge across all staff categories. Institutionalizing BLS education, particularly with tailored approaches for lower-literacy groups, could strengthen emergency preparedness in university settings.